Mine reclamation bonding and environmental insurance. (19th June 2007) - Poulin, Richard; Jacques, Michel
Mineral extraction is normally followed by rehabilitation of the mined area. A growing number of jurisdictions are using environmental bonding to provide financial assurance that rehabilitation will be carried out as agreed at the permitting stage. The current practice in environmental bonding for mining is critically reviewed. In theory, it is an efficient economic enforcement mechanism but has shown shortcomings in its application. Elements of a solution are identified through the emergence of environmental insurance. The use of insurance as a complement to bonding could prove beneficial by creating a useful framework and by reducing the risk for the public and the environment. We propose a simple model showing how risk could be quantified.